Frequency of Multidrug-Resistant Microorganisms Associated with Bacterial Coinfections in Hospitalized Patient with Covid-19: A Literature Review - Maria Walcleanes Magalhães de Oliveira; Júlio César Sousa Prado; Martinair Santana da Silva; Maria Gleiciane de Queiroz Martins; Francisco Cesar Barroso Barbosa (Archives of Current Research International, 2024)
Patients with a doença do coronavírus 2019 (COVID-19) may be at risk of associated bacterial co-infections, and the involvement of multidrug-resistant (MDR) microorganisms in these cases can lead to an increase in morbidity and mortality rates. The objective of this study was to describe the frequency of the main MDR microorganisms associated with bacterial co-infections in patients hospitalized with COVID-19. To this end, we carried out a search in the PubMed and Regional Portal of the Virtual Health Library (VHL) databases, from December 2019 to September 2023, with the keywords COVID-19, co-infection and multidrug-resistant microorganism. Of the 535 articles initially found, only 14 were selected for analysis. Gram-negative bacteria were most frequently involved in bacterial co-infections in patients with COVID-19 (70%). Among these, Klebsiella pneumoniae and Acinetobacter baumannii predominated, with 85.71% and 78.57%, respectively. Among gram-positive bacteria, Staphylococcus aureus (71.42%) was the most common. Among MDR microorganisms, the prevalent species were carbapenem-resistant gram-negative bacilli (32%) and methicillin-resistant S. aureus (85.7%). Furthermore, a higher frequency of MDR microorganisms was observed in patients with COVID-19 in intensive care units (ICU). Thus, the findings of the present study indicate the need for attention to infections caused by multidrug-resistant microorganisms in critically ill patients with COVID-19.